KERENTANAN DAN STRATEGI ADAPTASI MASYARAKAT TEPI WADUK DESA PONGKAI ISTIQOMAH TERHADAP DAMPAK KEKERINGAN DARI PERUBAHAN IKLIM - Henny Daniaty; Sujianto Sujianto; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2019)
Climate change that occurred in the Koto Panjang hydropower reservoir area was triggered by high land use change and was driven by minimal rainfall. The impact of drought occurred. The reservoir water is shrinking and other water sources are also shrinking, especially the Pongkai Istiqomah village located on the edge of the reservoir. These water sources in the form of Binamang River water and residents' well water are also shrinking. As a result, people's lives are disrupted, both in meeting the needs of clean water, bathing, washing and toilet and disrupting the economic conditions of the community. If the community's adaptability is beyond the optimal level, then the community can be said to be vulnerable. Therefore, it is important to know the level of vulnerability and adaptation strategies that can be applied. This research was conducted in July 2017 to July 2018. The research method used was a quantitative method with a descriptive approach. Data collection is done by interview and observation techniques. The interview technique was carried out on 40 (forty) respondents who were guided by a questionnaire. Analyzing the data is done by giving a score for each vulnerability criterion, namely exposure (E, exposure), sensitivity (sensitivity, S) and Adaptive Capacity (AC). The results showed that the Pongkai Istiqomah Village community had a level of vulnerability according to Heston. Y.P (2014) is included in the category of Medium Vulnerability with a score of 0.51. However, this condition cannot be underestimated, so an adaptation strategy that has been analyzed using SWOT-AHP is needed. The results are three priority strategies that have been assessed in terms of percentages namely water harvesting (43.8%), revitalization of existing tools (24.6%) and community empowerment (4.8%). To realize the adaptation trategy, there needs to be support from the Regional Government in the form of policies related to village-based development planning and sustainable community capacity building.